Intraoperative optical coherence tomography angiography for intraocular surgery - Cheng, Dan; Zhang, Ziyi; Qiao, Yilin; Ye, Yufeng; Zhu, Xueying; Ruan, Kaiming; Shen, Meixiao; Liu, Kaiyuan; Tao, Jiwei; Chen, Yiqi; Shen, Lijun; Li, Peng (Frontiers in Physics, 2023)
We present an intraoperative optical coherence tomography angiography (iOCTA) system combined with the GPU-based real-time data processing pipeline for real-time monitoring of retinal blood flow during intraocular surgery. The feasibility of this system was confirmed through fundus angiography imaging in 12 rabbit eyes during simulated surgeries in 4 groups, 30 mmHg IP, 60 mmHg IP, 100 mmHg IP, and control groups. The eyes were removed after seven days. Retinal ganglion cell (RGC) damage was analyzed histologically. The OCTA signal and the RGCs decreased significantly in the 60 and 100 mmHg groups. The system can real-timely monitor the human retinal vasculature in high-resolution images and help surgeons to make decision during intraocular surgery.